The balance between child autonomy and parental autonomy in Malawi; an analysis of the Child Care, Protection and Justice Act - Mkandawire, Leona Temwa (Department of Public Law, 2018)
For a long time children have been considered to be vulnerable persons, incapable of making rational decisions. As a result, decisions have been made for children by other people such as their parents or guardians. In most African societies, including Malawi, children remain largely voiceless and dependent on their parents who view their role mainly as being to protect children from their own actions and actions of other people. However, international law considers children as autonomous persons capable of making their own decisions. Thus, it requires states to recognise the autonomy a child although it also recognises that parents are free to raise children the way they want. Both the CRC and the African Children's Charter recognise children as bearers of rights and guarantee their right to take part in decisions that affect them. These treaties also recognise the principles of the best interests of the child, non-discrimination, and the child's right to life, survival and development. This thesis finds that while the best interests' principle has been domesticated under the Constitution, the other principles are not explicitly entrenched in the Constitution or under the Child Care, Protection and Justice Act. At best, they can be implied in other provisions of the Act. Overall, the Child Care, Protection and Justice Act leans towards enhancing the parental autonomy in child rearing and institutional protection of children rather than towards the emancipation of children in accordance with their evolving capacities.